TINGKAT KECUKUPAN MODAL, DANA PIHAK KETIGA DAN RISIKO BISNIS TERHADAP PROFITABILITAS BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Diah Ayu Larasati; Marlina Marlina; Siti Hidayati (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
This study is a quantitative research that aims to determine the effect of capital adequacy rate, third party funds and business risk on profitability in banking companies listed on the Indonesia Stock Exchange period 2013-2016. The population in this study is a banking company listed on the Indonesia Stock Exchange period 2013-2016. Sample selection is done by using purposive sampling method. The sample used in this study are 14 national private commercial banks listed on Indonesia Stock Exchange period 2013-2016. The type of data used is secondary data and the method of analysis used is panel data regression using EViews 9.0 program. The result of regression panel data analysis using significance level of 0.05 indicates that the level of capital adequacy and business risk affect the profitability of the bank. While third party funds have no effect on bank profitability.